(untitled) (Journal of Computational Mathematics, 1992)
A new stability inequality for velocity-pressure F.E. approximations of Stokes (or Navier-Stokes) problems is presented in this paper. It is proved that the inequality holds if the so-called patch test of rank non-deficiency is passed. As a use of the new criterion, the stability of various new and old combinations of velocity interpolations with pressure interpolations is discussed.